Severely impaired hippocampal neurogenesis associates with an early serotonergic deficit in a BAC ?-synuclein transgenic rat model of Parkinson's disease - Kohl, Zacharias; Ben Abdallah, Nada; Vogelgsang, Jonathan; Tischer, Lucas; Deußer, Janina; Amato, Davide; Anderson, Scott; Müller, Christian P.; Riess, Olaf; Masliah, Eliezer; Nuber, Silke; Winkler, Jürgen (Neurobiology of Disease, 2016)
Parkinson's disease (PD) is a multisystem disorder, involving several monoaminergic neurotransmitter systems resulting in a broad range of motor and non-motor symptoms. Pathological hallmarks of PD are the loss of dopaminergic neurons and the accumulation of alpha-synuclein, however also being present in the serotonergic raphe nuclei early in the disease course. The dysfunction of the serotonergic system projecting to the hippocampus may contribute to early non-motor symptoms such as anxiety and depression. The adult hippocampal dentate gyrus (DG), a unique niche of the forebrain continuously generating new neurons, may particularly present enhanced susceptibility towards accumulating alpha-synuclein levels. The underlying molecular mechanisms in the context of neuronal maturation and survival of new-born neurons are yet not well understood. To characterize the effects of overexpression of human full-length alpha-synuclein on hippocampal cellular and synaptic plasticity, we used a recently generated BAC alpha-synuclein transgenic rat model showing important features of PD such as widespread and progressive alpha-synuclein aggregation pathology, dopamine loss and age-dependent motor decline. At the age of four months, thus prior to the occurrence of the motor phenotype, we observed a profoundly impaired dendritogenesis of neuroblasts in the hippocampal DG resulting in severely reduced survival of adult new-born neurons. Diminished neurogenesis concurred with a serotonergic deficit in the hippocampus as defined by reduced levels of serotonin (5-HT) 1B receptor, decreased 5-HT neurotransmitter levels, and a loss of serotonergic nerve terminals innervating the DG/CA3 subfield, while the number of serotonergic neurons in the raphe nuclei remained unchanged. Moreover, alpha-synuclein overexpression reduced proteins involved in vesicle release, in particular synapsin-1 and Rab3 interacting molecule (RIM3), in conjunction with an altered ultrastructural architecture of hippocampal synapses. Importantly, BAC alpha-synuclein rats showed an early anxiety-like phenotype consisting of reduced exploratory behavior and feeding. Taken together, these findings imply that accumulating alpha-synuclein severely affects hippocampal neurogenesis paralleled by impaired 5-HT neurotransmission prior to the onset of aggregation pathology and overt motor deficits in this transgenic rat model of PD.
EVALuna2:23681